Manufacturing method of dry and hard particle forage for boer goat in lactation period - HE YI'AN (2017)
The invention provides a manufacturing method of dry and hard particle forage for a boer goat in a lactation period. 1) The forage is made from the following raw materials, by weight part, 47-53 parts of fish meal, 75-85 parts of Chinese herbal medicine grass meal, 95-105 parts of dried stillage powder, 143-157 parts of corn straw powder, 143-157 parts of soybean meal, 143-157 parts of alfalfa meal, 190-210 parts of millet, 190-210 parts of oats, 335-365 parts of corn, 9.5-10.5 kg of sodium bicarbonate, 9.5-10.5 kg of calcium hydrogen phosphate and 9.5-10.5 kg of salt. 2) The dry and hard particle forage is made from the materials in the step 1) according to a specific method. The manufacturing method has the beneficial effects that the nutrition is balanced, and the phenomenon that the goat is fastidious about food is prevented. Through addition of millet, oats and dried stillage powder, the palatability of the forage is improved, and the food consumption of the boer goat is increased. Millet, motherwort her